PPM1D activity promotes the replication stress caused by cyclin E1 overexpression - Martinikova, Andra S; Stoyanov, Miroslav; Oravetzova, Anna; Kok, Yannick P; Yu, Shibo; Dobrovolna, Jana; Janscak, Pavel; van Vugt, Marcel; Macurek, Libor (Molecular oncology, 2024)
Oncogene-induced replication stress has been recognized as a major cause of genome instability in cancer cells. Increased expression of cyclin E1 caused by amplification of the CCNE1 gene is a common cause of replication stress in various cancers. Protein phosphatase magnesium-dependent 1 delta (PPM1D) is a negative regulator of p53 and has been implicated in termination of the cell cycle checkpoint. Amplification of the PPM1D gene or frameshift mutations in its final exon promote tumorigenesis. Here, we show that PPM1D activity further increases the replication stress caused by overexpression of cyclin E1. In particular, we demonstrate that cells expressing a truncated mutant of PPM1D progress faster from G1 to S phase and fail to complete licensing of the replication origins. In addition, we show that transcription-replication collisions and replication fork slowing caused by CCNE1 overexpression are exaggerated in cells expressing the truncated PPM1D. Finally, replication speed and accumulation of focal DNA copy number alterations caused by induction of CCNE1 expression was rescued by pharmacological inhibition of PPM1D. We propose that increased activity of PPM1D suppresses the checkpoint function of p53 and thus promotes genome instability in cells expressing the CCNE1 oncogene.
Keywords: Neoplasms; nádory; nestabilita genomu; Tumor Suppressor Protein p53; Protein Phosphatase 2C; lidé; cyklin E; proteinfosfatasa 2C; Cyclin E; Genomic Instability; nádorový supresorový protein p53; Humans